Crisis management: Regional approaches to geopolitical crises and natural hazards. (31st August 2021) - Raikes, Jonathan; Smith, Timothy F.; Powell, Neil; Thomsen, Dana C.; Friman, Eva; Kronlid, David; Sidle, Roy
Abstract: Crisis management planning and response can be improved by regional governments and organisations learning from one another. Specifically, comparative learning may be a benefit when groups understand the perceived effectiveness of various regional approaches when responding to different types of hazards. This article presents findings from a comparative case study analysis of regional governance perspectives of crisis management for geopolitical events and natural hazards in the Sunshine Coast, Australia, and Gotland, Sweden. Data were collected and analysed using document analyses and semi‐structured interviews with regional practitioners. It was found that regional crisis management is increasingly influenced by global processes that are affecting the scales and characteristics of crises. As a result, prospective regional governance must evolve to include more international perspectives in crisis management and account for activities and processes that take place beyond arbitrary political boundaries. Abstract : Crisis management planning and response can be improved by regions learning from one another. This paper presents the findings of a comparative study on regional crisis management approaches for geopolitical crises and natural hazards in the Sunshine Coast, Australia, and Gotland, Sweden, arguing that global processes are increasingly challenging the scalar politics for conventional crisis management and related policy areas. Prospective regional crisis management would benefit from perspectives that account for the activities and processes occurring beyond these arbitrary political boundaries for managing conventional policy problems.